SUKIPT UPSI Tanjong Malim 18 Ogos 2022 Edisi 6 - Jawatankuasa Media, Buletin dan Publisiti (Putrajaya, 2022)
SUKIPT UPSI Tanjong Malim 18 Ogos 2022 Edisi 6 by Jawatankuasa Media, Buletin dan Publisiti